Is the Universe a Hologram? : Scientists Answer the Most Provocative Questions - Plasencia, Adolfo (Book collections on Project MUSE., 2017)
Conversations with scientists, conducted by a veteran science writer, addressing such issues as intelligence, consciousness, global warming, energy, changing the past, and even the philosophical curveball, "Is the universe a hologram?"